Face recognition based on singular valued decomposition and back progagation neural network - Rasied, Thaahirah S. M.; Khalifa, Othman Omran; Kamarudin, Yuslina (2005)
This paper presents a developed face recognition system. The method used singular valued decomposition as images feature extractor and back propagation neural networks as its classifier. The back propagation training parameters are varied in order to find the best parameter with the highest performance accuracy. The results from experiments have showed that combinations of both methodologies give good recognition rate and therefore considered as an effective face recognition system.